A STUDY ON SECOND GRADE MHD FLOW AND HEAT TRANSFER WITH VISCOUS AND OHMIC DISSIPATIONS OVER AN EXPONENTIALLY STRETCHING SHEET WITH - Sanjayanand, Emmanuel (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Momentum boundary layer of viscoelastic second grade fluid taken into consideration with the effect of uniform transverse magnetic field and normal electric field also included in the analysis. Thermal boundary layer formed over the non-isothermal boundary wall, with viscous dissipation and Ohmic dissipation due to transverse magnetic field and electric field has been investigated. The highly non-linear momentum boundary layer equation and thermal boundary layer equation are converted into similarity equations and then solved numerically by employing fifth order Runge-Kutta-Fehlberg method with shooting.